The epichaperome is an integrated chaperome network that facilitates tumour survival - Rodina, Anna (Nature, 2016)
Transient, multi-protein complexes are important facilitators of cellular functions. This includes the chaperome, an abundant protein family comprising chaperones, co-chaperones, adaptors, and folding enzymes—dynamic complexes of which regulate cellular homeostasis together with the protein degradation machinery(1–6). Numerous studies have addressed the role of chaperome members in isolation, yet little is known about their relationships regarding how they interact and function together in malignancy(7–17). As function is probably highly dependent on endogenous conditions found in native tumours, chaperomes have resisted investigation, mainly due to the limitations of methods needed to disrupt or engineer the cellular environment to facilitate analysis. Such limitations have led to a bottleneck in our understanding of chaperome-related disease biology and in the development of chaperome-targeted cancer treatment. Here we examined the chaperome complexes in a large set of tumour specimens. The methods used maintained the endogenous native state of tumours and we exploited this to investigate the molecular characteristics and composition of the chaperome in cancer, the molecular factors that drive chaperome networks to crosstalk in tumours, the distinguishing factors of the chaperome in tumours sensitive to pharmacologic inhibition, and the characteristics of tumours that may benefit from chaperome therapy. We find that under conditions of stress, such as malignant transformation fuelled by MYC, the chaperome becomes biochemically ‘rewired’ to form a network of stable, survival-facilitating, high-molecular-weight complexes. The chaperones heat shock protein 90 (HSP90) and heat shock cognate protein 70 (HSC70) are nucleating sites for these physically and functionally integrated complexes. The results indicate that these tightly integrated chaperome units, here termed the epichaperome, can function as a network to enhance cellular survival, irrespective of tissue of origin or genetic background. The epichaperome, present in over half of all cancers tested, has implications for diagnostics and also provides potential vulnerability as a target for drug intervention.